Study protocol: a double blind placebo controlled trial examining the effect of domperidone on the composition of breast milk [NCT00308334] - Campbell-Yeo Marsha L; Allen Alexander C; Joseph K S; Ledwidge Joyce M; Allen Victoria M; Dooley Kent C (BMC, 2006)
Abstract Background Domperidone, a drug that enhances upper gastric motility, is an anti-dopaminergic medication that also elevates prolactin levels. It has been shown to safely increase the milk supply of lactating women. To date, researchers have analyzed the effects of domperidone on lactating woman with respect to the quantity of their milk production, adverse effects, and drug levels in the breast milk. However, the effect of domperidone on the macronutrient composition of breast milk has not been studied and current guidelines for fortification of human milk for premature infants do not distinguish between those women using or those not using domperidone. The purpose of this study is to evaluate the effect of domperidone (given to lactating mothers of very preterm infants) on the macronutrient composition of breast milk. Methods/Design Mothers of infants delivered at less than 31 weeks gestation, who are at least 3 weeks postpartum, and experiencing lactational failure despite non-pharmacological interventions, will be randomized to receive domperidone (10 mg three times daily) or placebo for a 14-day period. Breast milk samples will be obtained the day prior to beginning treatment and on days 4, 7 and 14. The macronutrient (protein, fat, carbohydrate and energy) and macromineral content (calcium, phosphorus and sodium) will be analyzed and compared between the two groups. Additional outcome measures will include milk volumes, serum prolactin levels (measured on days 0, 4, and 10), daily infant weights and breastfeeding rates at 2 weeks post study completion and at discharge. Forty-four participants will be recruited into the study. Analysis will be carried out using the intention to treat approach. Discussion If domperidone causes significant changes to the nutrient content of breast milk, an alteration in feeding practices for preterm infants may need to be made in order to optimize growth, nutrition and neurodevelopment outcomes.